Odpowiedzi

2009-10-05T15:36:43+02:00
A. x+2y=9
y-1=3x

x+2y=9
y-3x=1 /*(-2)

x+2y=9
6x-2y=-2

7x=7 /:7
x=1
Szukamy y:
x+2y=9
7+2y=9
2y=9-7
2y=2 /:2
y=1

b. x-y=2
½x-1=¼y

x-y=2
1/2x-1/4y=1 /(-2)

x-y=2
-x+1/2y=-2

-1/2y=0 / *2
y=0

x-y=2
x-0=2
x=2

c. -x-y=2
2(3x+y)=-20

-x-y=2 /*2
6x+2y=-20

-2x-2y=4
6x+2y=-20

4x= -16 /:4
x=-4

-2x-2y=4
-2*(-4)-2y=4
8-2y=4
-2y=-4 /:(-2)
y=2

d. 4x+3y=54
⅓x=4(1+⅛y)

4x+3y=54
1/3x=4+1/2y

4x+3y=54
1/3x-1/2y=4 /*6

4x+3y=54
2x-3y=24

6x=78 /:6
x=13

4x+3y=54
4*13+3y=54
52+3y=54
3y=54-52
3y=2 /:3
y=2/3
Pozdrawiam;)